CXCR7 influences the migration of B cells during maturation. (19th February 2014) - Humpert, Marie‐Luise; Pinto, Dora; Jarrossay, David; Thelen, Marcus
<x xml:space="preserve">Abstract</x> The atypical chemokine receptor CXCR7 binds the chemokines CXCL12 and CXCL11. The receptor is widely expressed and was shown to tune CXCR12‐induced responses of CXCR4. Here, the function of CXCR7 was examined at late stages of human B‐cell maturation, when B cells differentiate into Ab‐secreting plasmablasts. We identified two populations of CXCR7+ cells in tonsillar lymphocytes, one being presumably memory B cells or early plasmablasts (FSClowCD19+CD38mid) and the other being plasmablasts or early plasma cells (FSChighCD19+CD38+). CXCR7 is expressed on CD19+CD27+ memory B cells, on CD19+CD38+CD138− and intracellular immunoglobulin high plasmablasts, but not on CD19+CD138+icIghigh plasma cells. The differential expression pattern suggests a potential contribution of the scavenger receptor in final B‐cell maturation. On in vitro differentiating B cells, we found a marked inverse correlation between CXCR7 and CXCR5 cell surface levels, whereas expression of CXCR4 remained almost constant. Migration assays performed with tonsillar mononuclear cells or in vitro differentiated cells revealed that inhibition of CXCR7 markedly increases chemotaxis toward CXCL12, especially at late stages of B‐cell maturation. Chemotaxis was attenuated in the presence of CXCR4 antagonists, confirming that migration is CXCR4 mediated. Our findings unequivocally demonstrate a novel role for CXCR7 in regulating the migration of plasmablasts during B‐cell maturation.